Dualism of Competences in The Settlement of Child Abusement Cases in Aceh: Case Number 231/Pid.Sus/2018/ PN Bna and 005/JN/2017/Ms-Lgs [Dualisme Kewenangan Penyelesaian Perkara Tindak Pidana Pencabulan Anak di Aceh: 231/Pid.Sus/2018/ PN Bna dan 005/JN/2017/Ms-Lgs] - Rispalman Rispalman; Syahrizal Abbas; Desi Ariani (Islamic Criminal Law Department, Faculty of Sharia and Law, UIN Ar-Raniry, 2021)
Abstract: There is a dualism of competencies in the settlement of cases of sexual abuse of children in Aceh. The practice of dualism of competencies occurs in the settlement of cases of criminal acts of sexual abuse against children in Aceh where case Number 231/Pid.Sus/2018/PN Bna was resolved in the Banda Aceh District Court and case Number 005/JN/2017/Ms-Lgs was resolved in the Mahkamah Syar'iyah Langsa. The research questions are why there is the dualism of authority in resolving cases of child molestation in Aceh and what is the juridical basis for the Banda Aceh District Court and the Langsa Mahkamah Syar'iyah Court in adjudicating cases of child abuse. This research uses normative juridical research. Dualism occurs because the Qanun Jinayat and the Child Protection Law (UUPA) regulate the sexual abuse of children. The juridical basis of the District Court in the settlement of cases of criminal acts of sexual abuse against children in case Number 231/Pid.Sus/2018/PN Bna uses Law Number 35 of 2014 concerning Child Protection (UUPA), and the juridical basis of the Syar'iyah Court in the settlement cases of criminal acts of sexual abuse against children in case Number 005/JN/2017/Ms-Lgs using Article 47 of Aceh Qanun Number 6 of 2014 concerning Jinayat Law. The judicial process against Aceh Qanun Number 6 of 2014 concerning Jinayat Law was carried out at the Syar'iyah Court. The norm that has the authority to adjudicate is the Syar'iyah Court by implementing the Qanun Jinayat. Abstrak: Terdapat dualisme kewenangan dalam penyelesaian perkara tindak pidana pencabulan terhadap anak di Aceh. Praktiknya dualisme kewenangan terjadi dalam penyelesaian perkara tindak pidana pencabulan terhadap anak di Aceh dimana pada perkara Nomor 231/Pid.Sus/2018/PN Bna diselesaikan di Pengadilan Negeri Banda Aceh dan perkara Nomor 005/JN/2017/Ms-Lgs di selesaikan di Mahkamah Syar’iyah Langsa. Rumusan masalah dalam penelitian skripsi ini adalah mengapa terjadi dualisme kewenangan dalam penyelesaian perkara tindak pidana pencabulan terhadap anak di Aceh dan apa dasar yuridis Pengadilan negeri Banda Aceh dan Mahkamah Syar’iyah Langsa dalam mengadili perkara pencabulan terhadap anak. Penelitian ini menggunakan penelitian yuridis normatif. Dualisme terjadi dikarenakan Qanun Jinayat dan Undang-undang Perlindungan Anak (UUPA) mengatur pencabulan terhadap anak. Adapun landasan yuridis Pengadilan Negeri dalam penyelesaian perkara tindak pidana pencabulan terhadap anak pada perkara Nomor 231/Pid.Sus/2018/PN Bna menggunakan Undang-undang Nomor 35 Tahun 2014 tentang Perlindungan Anak (UUPA), dan landasan yuridis Mahkamah Syar’iyah dalam penyelesaian perkara tindak pidana pencabulan terhadap anak pada perkara Nomor 005/JN/2017/Ms-Lgs menggunakan Pasal 47 Qanun Aceh Nomor 6 Tahun 2014 tentang Hukum Jinayat. Proses peradilan terhadap Qanun Aceh Nomor 6 Tahun 2014 tentang Hukum Jinayat dilaksanakan di Mahkamah Syar’iyah. Secara norma yang berwenang mengadili ialah Mahkamah Syar’iyah dengan menerapkan Qanun Jinayat.